1994
DOI: 10.1159/000126634
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-1-Noradrenergic Inhibition of Growth Hormone Secretion Is Mediated through the Paraventricular Hypothalamic Nucleus in Male Rats

Abstract: In the present work we investigated a possible role of an α1-noradrenergic (NA) pathway involving the hypothalamic paraventricular nucleus (PVN) in the central regulation of growth hormone (GH) release. A week after bilateral electrolytic lesions of the PVN, pulsatile GH-secretory patterns were monitored in unanesthetized, freely moving control or lesioned male rats. While the pulsatility of GH secretion was maintained, the amplitude of the pulses and the area under the curve during an 8-hour sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…The α 1-adrenergic system exerts important eff ects on pituitary secretion in humans: administration of α 1-adrenergic agonists stimulate the secretion of Prolactin, Thyroid-Stimulating Hormone, and Adrenocorticotropic Hormone, whereas no convincing evidences have been found in humans in the control of Gonadotrophins secretion ( al-Damluji, 1993 ). An inhibitory eff ect of α 1-adrenergic agonists on Growth Hormone (GH) secretion would be compatible with the data obtained in rats ( Cella et al, 1987 ;Mounier et al, 1994 ) and dogs ( Cella et al, 1984 ). However, only a non-signifi cant decrease of GH concentrations after α 1-adrenergic agonist administration has been described in humans ( al-Damluji, 1993 ; al-Damluji and Francis, 1993 ).…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…The α 1-adrenergic system exerts important eff ects on pituitary secretion in humans: administration of α 1-adrenergic agonists stimulate the secretion of Prolactin, Thyroid-Stimulating Hormone, and Adrenocorticotropic Hormone, whereas no convincing evidences have been found in humans in the control of Gonadotrophins secretion ( al-Damluji, 1993 ). An inhibitory eff ect of α 1-adrenergic agonists on Growth Hormone (GH) secretion would be compatible with the data obtained in rats ( Cella et al, 1987 ;Mounier et al, 1994 ) and dogs ( Cella et al, 1984 ). However, only a non-signifi cant decrease of GH concentrations after α 1-adrenergic agonist administration has been described in humans ( al-Damluji, 1993 ; al-Damluji and Francis, 1993 ).…”
Section: Introductionsupporting
confidence: 61%
“…Interestingly, α 1-adrenoceptors are found in high density in most regions of the rat hypothalamus ( Leibowitz et al, 1982 ). Moreover, in animal models the methoxamine-induced GH decrease is abolished by pretreatment with anti somatostatin antibodies ( Cella et al, 1987 ) and by the bilateral lesion of the hypothalamic periventricular nucleus ( Mounier et al, 1994 ) (which contains somatostinergic neurons), thus suggesting that the stimulation of α 1-adrenoceptors inhibits GH secretion via an increased release of hypothalamic somatostatin into the portal blood. Since human hypothalamus contains α 1-adrenoceptors ( Wilcox et al, 1990 ), we could speculate that a similar mechanism may occurs in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas our data strongly suggest direct input to both GHRH and SRIF cells from the noradrenergic system, indirect regulation is also possible. One study (41) in male rats showed that α 1 noradrenergic inhibition of GH is mediated through the paraventricular nucleus. This nucleus receives direct noradrenergic input from the brainstem in rodents (34–36) and sheep (M. R. Namavar and I. J. Clarke, unpublished results) and also sends afferents to the ARC (36).…”
Section: Discussionmentioning
confidence: 99%
“…This nucleus receives direct noradrenergic input from the brainstem in rodents (34–36) and sheep (M. R. Namavar and I. J. Clarke, unpublished results) and also sends afferents to the ARC (36). Thus, noradrenergic regulation of GHRH cells may be indirect, via the paraventricular nucleus (41), but the extent of afferent connection to the ARC and the expression of adrenergic receptors in the paraventricular nucleus of the sheep remain to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…It is also noteworthy that heart failure itself may lead to alterations in GH/IGF-I axis, leading to decreased serum levels of IGF-I and IGFBP-3, either due to reduced GH secretion or resistance. A relative GH deficiency state is most likely due to alteration of neuroregulation of GH secretion due to activation of other neurohumoral processes in heart failure, such as activation of central sympathetic outflow, which activates neurons in the paraventricular nucleus of the hypothalamus, resulting in increased somatostatin release (199)(200)(201)(202)(203). The role for increased somatostatinergic tone is supported by the observation that patients with DCM have a reduced GH response to GHRH, but normal response to hexarelin (204), which may stimulate GH secretion independent of GHRH (149).…”
Section: Gh Treatment Of Heart Failure Due To Dilated Cardiomyopathymentioning
confidence: 99%